Monoaminergic Modulation of Cortical Excitability - Tseng, Kuei-Yuan.; Tseng, Kuei-Yuan.; Atzori, Marco.; Atzori, Marco. (Springer US : Imprint: Springer, 2007)
Monoaminergic Modulation of Cortical Excitability serves as an integrative and comprehensive comparison of the diverse and complex modulatory action of dopamine, noradrenaline, and serotonin receptors in the cortex. The volume is organized into several sections offering a broad spectrum of opinions on how the monoamine systems affect cortical function from a cellular/sub-cellular level to a system level. The complexity of these interactions are discussed in light of recent data showing how disruption of these systems dramatically affects the memory formation and information processing in the cortex. About the Editors: Dr. Kuei Y. Tseng is Assistant Professor in the Department of Cellular and Molecular Pharmacology at Rosalind Franklin University of Medicine and Science, The Chicago Medical School, North Chicago, IL, USA. Dr. Marco Atzori is Assistant Professor at the School for Behavioral and Brain Sciences at the University of Texas, Dallas, TX, USA.